Pluteus aurantioruber, a new species of Pluteus section Celluloderma (Pluteaceae) from China - Xu, Jiang; Hosen, Md. Iqbal; Zhang, Ming; Li, Tai-Hui (Phytotaxa, 2023)
Pluteus aurantioruber from southern China (Guangdong Province) is described as a new species. It is characterized by a bright orange-red to orange pileus, a reddish orange, orange, yellowish to semi-translucent stipe covered with tiny scales formed by clustered, clavate to fusiform caulocystidia, 26‒50 × 10‒21 μm, broadly ellipsoid to subglobose basidiospores, 6–8 × 5–7 μm, clavate and rostrate cheilocystidia, a hymeniderm to epithelium type pileipellis, and growing in soil or with moss. Data from the nuclear ribosomal internal transcribed spacer (nrITS) region shows that this species is nested in Pluteus sect. Celluloderma and grouped with the other species with rostrate cheilocystidia. A comprehensive description and illustrations are provided, with its phylogenetic placement based on nrITS also evaluated and including comparison to morphologically similar taxa and phylogenetically related species.